Review: Cultural Difference and Equal Dignity - Jaggar, Alison M. (The Hastings Center report, 1994)
Multiculturalism and “The Politics of Recognition.” An Essay by Charles Taylor with commentary by Amy Gutmann, editor, Steven C. Rockefeller, Michael Walzer, and Susan Wolf.